Dashavatara Temple at Deogarh - Temples of India Project Team (Jio Institute, 2024)
Within a quarter century, the Dashavatara Temple at Deogarh (c. 525 CE) expanded upon the concept of the unmanifest becoming manifest, featuring an elaborate symbolic program celebrating the multiple manifestations of the deity, in this case Vishnu. Image courtesy: Wikimedia Commons